2018
DOI: 10.1242/jcs.212803
|View full text |Cite
|
Sign up to set email alerts
|

Integrin activity in neuronal connectivity

Abstract: The formation of correct synaptic structures and neuronal connections is paramount for normal brain development and a functioning adult brain. The integrin family of cell adhesion receptors and their ligands play essential roles in the control of several processes regulating neuronal connectivity - including neurite outgrowth, the formation and maintenance of synapses, and synaptic plasticity - that are affected in neurodevelopmental disorders, such as autism spectrum disorders (ASDs) and schizophrenia. Many A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 165 publications
(213 reference statements)
2
103
0
1
Order By: Relevance
“…Here, the AP model exhibited altered expression of multiple axonal guidance molecules (SLIT2, EPHA8, EPHA5, EPHB4, and ROBO2). Integrin receptors and their ligands are cell adhesion molecules that control synaptic development and plasticity and can also be disrupted in ASD (53,54). The AP model exhibited downregulation of a suite of genes involved in integrin signaling, including ITGA1, ITGA2, ITGA3, ITGA5, ITGA9, ITGB3, ITGB4, and ITGB5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the AP model exhibited altered expression of multiple axonal guidance molecules (SLIT2, EPHA8, EPHA5, EPHB4, and ROBO2). Integrin receptors and their ligands are cell adhesion molecules that control synaptic development and plasticity and can also be disrupted in ASD (53,54). The AP model exhibited downregulation of a suite of genes involved in integrin signaling, including ITGA1, ITGA2, ITGA3, ITGA5, ITGA9, ITGB3, ITGB4, and ITGB5.…”
Section: Discussionmentioning
confidence: 99%
“…As a proposed contributor to ASD disease etiology, a treatment option currently being explored to reduce behavioral deficits and ameliorate brain structural abnormalities involves use of pharmacological modulators of WNT signaling (19,55,58). Here, we identified 17 differentially regulated WNT signaling-related genes in transcriptomic comparisons between the AP vs UM and Formation of synaptic circuits involves multiple steps, including axonal guidance, neurite outgrowth, growth cone targeting, and synapse formation and maturation (53,61). In our study, the AP exhibited reduced neurite outgrowth and neurite length and concordant dysregulation of genes mediating axonal guidance, gap junctional connectivity, and neuritogenesis, congruent cellular and molecular alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings indicate that a state of neuronal hyperconnectivity may play an essential role in the etiology of ASD (Tang et al, 2014;Zaslavsky et al, 2019;Zhang et al, 2016). Many genes which have been associated with ASD and changes in neuronal connectivity belong to the integrin family (Lilja and Ivaska, 2018) and Ingenuity Pathway Analysis in myotube cells with MEF2 downregulations revealed that integrin signaling is one of the few pathways targeted by all MEF2 isoforms (Estrella et al, 2015). One member of this family is integrin ß1, a cell surface receptor linking the actin cytoskeleton with the extracellular matrix (ECM), mediating cell adhesion and thereby information that influences cellular morphology (Werner and Werb, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This integrin is known to join with the β1 subunit to form the primary fibronectin receptor α5β1 and, in the central nervous system, is involved in the process of neuronal migration and in long-term potentiation (LTP). Inhibition or deletion of integrins, such as α3, α5, or β1, negatively affects synapse organization and impairs LTP (Dityatev et al, 2010;Marchetti et al, 2010;Lilja and Ivaska, 2018). As shown in Figure 4, integrin α5 immunoreactivity in cells cultured on glass had a cytoplasmatic localization near the perinuclear zone, while, in ECM-cultured cells (Figure 4B), its immunoreactivity appeared more distinctly expressed across the cell adhesion surface, particularly localized at the level of cytoplasmic projections.…”
Section: Effect Of Ecm On Cell Adhesion and Neuronal Markersmentioning
confidence: 94%